2012
DOI: 10.1109/led.2012.2210019
|View full text |Cite
|
Sign up to set email alerts
|

Bridged-Grain Solid-Phase-Crystallized Polycrystalline-Silicon Thin-Film Transistors

Abstract: Novel bridged-grain (BG) technique is applied in the fabrication of low-temperature solid-phase-crystallized polycrystalline-silicon thin-film transistors. As a result of improved current flow and reduction of high drain electric field, the subthreshold slope, threshold voltage, maximum field-effect mobility, leakage current, and on-off ratio are greatly improved. Mechanisms of BG conduction are studied in detail.Index Terms-Bridged grain (BG), polycrystalline silicon (poly-Si), thin-film transistors (TFTs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…Thin-Film Transistors technology [6]- [9] has been proposed and introduced to generate high-performance poly-Si TFTs. By selectively doping BG lines inside the active channel [6]- [9], grain size effect, shortchannel effect (SCE), and multijunction effect are beneficially exploited, resulting in excellent device electrical characteristics in terms of field-effect carrier mobility (μ FE ), threshold voltage (V th ), subthreshold swing (SS), and ON-current/OFFcurrent ratio (I ON /I OFF ).…”
Section: Characterization Of Dc-stress-induced Degradation In Bridgedmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin-Film Transistors technology [6]- [9] has been proposed and introduced to generate high-performance poly-Si TFTs. By selectively doping BG lines inside the active channel [6]- [9], grain size effect, shortchannel effect (SCE), and multijunction effect are beneficially exploited, resulting in excellent device electrical characteristics in terms of field-effect carrier mobility (μ FE ), threshold voltage (V th ), subthreshold swing (SS), and ON-current/OFFcurrent ratio (I ON /I OFF ).…”
Section: Characterization Of Dc-stress-induced Degradation In Bridgedmentioning
confidence: 99%
“…By selectively doping BG lines inside the active channel [6]- [9], grain size effect, shortchannel effect (SCE), and multijunction effect are beneficially exploited, resulting in excellent device electrical characteristics in terms of field-effect carrier mobility (μ FE ), threshold voltage (V th ), subthreshold swing (SS), and ON-current/OFFcurrent ratio (I ON /I OFF ). For these high-performance BG poly-Si TFTs, hitherto no systematical reliability studies have been performed and reported.…”
Section: Characterization Of Dc-stress-induced Degradation In Bridgedmentioning
confidence: 99%
“…Thus, previously, low-temperature polycrystalline silicon (poly-Si) was able to be used rather than a-Si:H in AMOLED. Three main low-temperature crystallization techniques are currently used: (1) solid-phase crystallization (SPC) [3], (2) metal-induced lateral crystallization (MILC) [4], and (3) excimer laser annealing (ELA) [5]. Although the SPC is the simplest technology among the other crystallization techniques, it needs to be performed by annealing at 600°C for 24 h, which results in a poor throughput for mass production.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed discussion of the processing steps was provided elsewhere [1][2] 11 , the surface potential extracted from sub-threshold I-V curves is shown in Fig. 1(b).…”
Section: Devices Parameters and I-v Characteristicsmentioning
confidence: 99%